2009
DOI: 10.1007/bf03256314
|View full text |Cite
|
Sign up to set email alerts
|

Study of NAT2 Gene Polymorphisms in an Indian Population

Abstract: The results suggested high variation in the frequencies of NAT2 alleles and genotypes within Indian populations, which influence plasma isoniazid concentrations. Further studies of the relationship between NAT2 genotypes and adverse drug events are required to make genotyping a helpful tool for optimizing the isoniazid therapeutic response and minimizing adverse drug reactions, particularly in countries with a high burden of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 43 publications
1
12
1
1
Order By: Relevance
“…Although there appeared to be a trend in the proportion of patients with sub-therapeutic INH concentrations, the differences were not significant. The drug concentrations observed in our study was higher than that reported from an earlier study from Mumbai, which could be because of differences in the INH dose used in these studies, 600 mg in the present study and 300 mg in the Mumbai study5.…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations
“…Although there appeared to be a trend in the proportion of patients with sub-therapeutic INH concentrations, the differences were not significant. The drug concentrations observed in our study was higher than that reported from an earlier study from Mumbai, which could be because of differences in the INH dose used in these studies, 600 mg in the present study and 300 mg in the Mumbai study5.…”
Section: Resultscontrasting
confidence: 89%
“…Several studies to date have documented the influence of NAT2 genotypes on plasma concentrations of INH251415. Drug-induced hepatotoxicity as well as adverse drug events have also been reported16.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,23]. On the other hand, the NAT2 polymorhism affects the rate of inactivation and, therefore, the concentration in blood of certain medicines, including antituberculosis drug isoniazid [34]. Thus, determination of the genotype/phenotype of NAT2 can serve as a supplementary method for improving the pharmacotherapy efficiency and minimization of side effects during treatment of certain diseases, for instance tuberculosis (TB).…”
mentioning
confidence: 99%